Deterrence and the tipping effect - Brown, Stephen E. (American journal of criminal justice, 1981)
Previous research has focused on certaintyznty of punishment as one. factor. upon which any dzterrent effect of punishment might be contingent and Auggested that it must reach a critical tipping level before the deterrent effect becomes evident. Using data on index crimes and clearance. rates for. Virginia cities and counties, bupport was found for both the. deterrent effect and the exlstenee of a tipping level. Attention was directed towand a more precise specification of the form of the tipping effect, suggesting that there is a single critical tipping level and that it occurs at a relatively low level of certainty of punihment.